PERAN CONTENT PLANNER DAN COPYWRITER PADA KAMPANYE “TERBUKA UNTUK SEMUA, BERGERAK BERSAMA WARGA #KULIKDIPORTALSAMAWA” SEBAGAI UPAYA BRAND COMMUNICATION UNTUK MENINGKATKAN BRAND AWARENESS SERTA USER PORTAL SEMARANG SATU DATA DAN SAMAWA (Semua Data Untuk Warga) - Iqbal Rosadi; Joyo Nur Suryanto Gono (Interaksi Online, 2026)
The campaign “Terbuka untuk Semua, Bergerak Bersama Warga #KulikdiPortalSAMAWA” was conducted to address the low brand awareness and utilization of Portal Semarang Satu Data and SAMAWA services managed by the Statistics Division of the Semarang City Communication and Informatics Office. Using an Integrated Marketing Communication (IMC) approach through social media, roadshows, webinars, and digital service optimization, the campaign involved the roles of content planner and copywriter in planning, producing, and maintaining message consistency. The results showed an increase in brand awareness of Portal Semarang Satu Data from 49.2% to 80% and SAMAWA from 12.3% to 75%, Instagram reach from 3,294 to 10,282, and a 35.2% increase in portal visitors. These results indicate that the campaign effectively improved awareness and utilization of Semarang City public data services.